The 2025–2030 Dietary Guidelines for Americans are associated with higher land, water and nitrogen use, and greenhouse gas emissions - Alon Shepon; Tamar Makov; David L. Katz; Gidon Eshel (Proceedings of the National Academy of Sciences, 2026)
Dietary guidelines form the foundation of federal food policy, informing programs such as the Supplemental Nutrition Assistance Program (SNAP), government food procurement, school meals, and military and hospital food services. The most recent guidelines, released in early 2026, advise avoiding “hyperprocessed” (generally known as ultraprocessed foods, UPFs), while also recommending higher overall protein intake chiefly from animal sources. Here, we quantified the greenhouse gas (GHG) emissions, freshwater use, land use, and nitrogen fertilizer use of adherence to these new guidelines in comparison to the current Mean American Diet (MAD). We constructed isocaloric diets with varying degrees of added protein intake and protein sources that are similar to current dietary patterns, but with no UPFs as recommended. We find that although eliminating ultraprocessed foods from the MAD could yield substantial environmental benefits—given their large share of total intake and animal-based makeup—the recommended increase in animal-based proteins, will more than offset this environmental dividend in GHG, land use, and nitrogen fertilizer use by as much as 32%, but not in water use (i.e., water use is lower by 7 to 19% than the MAD). Across all environmental metrics measured, favoring plants- over animal-based foods leads to better environmental outcomes. Overall, adherence to the 2025–2030 Dietary Guidelines for Americans would confer net environmental harm across most key metrics relative to the prevailing U.S. diet.